2022
DOI: 10.1016/j.jgo.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of geriatric oncology screening and geriatric assessment of older patients with cancer: A randomized clinical trial protocol (PROGNOSIS-RCT)

Abstract: Introduction: Comprehensive geriatric assessment (CGA) has been shown to reduce frailty in older patients in general. In older patients with cancer, frailty affects quality of life (QoL), physical function, and survival. However, few studies have examined the effect of CGA as an additional intervention to antineoplastic treatment. This protocol presents a randomized controlled trial, which aims to evaluate the effects of CGA-based interventions in older patients with cancer and Geriatric 8 (G8) identified frai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…CGA in older cancer patients indicates previously unknown geriatric problems in many patients (up to 50 %) and may alter treatment decisions in 10% to 20% of patients [26]. Among the domains of CGA, limitations in cognition, nutrition, function, and comorbidities have been shown to be important factors in diminishing OS in older cancer patients in several studies [27][28][29]. It has also been shown that comprehensive geriatric intervention for older cancer patients significantly improved OS and facilitated a return to their own home compared to conventional hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…CGA in older cancer patients indicates previously unknown geriatric problems in many patients (up to 50 %) and may alter treatment decisions in 10% to 20% of patients [26]. Among the domains of CGA, limitations in cognition, nutrition, function, and comorbidities have been shown to be important factors in diminishing OS in older cancer patients in several studies [27][28][29]. It has also been shown that comprehensive geriatric intervention for older cancer patients significantly improved OS and facilitated a return to their own home compared to conventional hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to include life expectancy as an inclusion criterion in studies focusing on patients undergoing palliative-intent treatment. Secondly, even though several steps were taken during the design of the study to ensure adequate patient inclusion, our inclusion was lower (181 of 523 eligible participants) than comparable studies [32,33]. Finally, since rehabilitation primarily took place in the municipalities, the time to initiation of physiotherapist-guided rehabilitation was not available in participants' medical records and, hence, not registered.…”
Section: Tablementioning
confidence: 98%
“…This open-label RCT was conducted in the oncologic outpatient clinic at Odense University Hospital, Denmark. The study protocol has previously been described in detail [33]. The study included patients who participated in a larger departmental cohort study with advanced solid cancers, initiating palliative therapy, age ≥ 70 years, and screened frail using the G8 (≤14 as cut-off score).…”
Section: Study Design and Populationmentioning
confidence: 99%